Migrant worker and Mental health in Nepal - Editor, The (Journal of Psychiatrists' Association of Nepal, 2014)
DOI: http://dx.doi.org/10.3126/jpan.v1i1.9917 Journal of Psychiatrists' Association of Nepal Vol.1(1) 2011